Peritoneal dialysis for chronic cardiorenal syndrome: Lessons learned from ultrafiltration trials - Kazory, Amir (World J Cardiol, 2015)
The current models of cardiorenal syndrome (CRS) are mainly based on a cardiocentric approach; they assume that worsening renal function is an adverse consequence of the decline in cardiac function rather than a separate and independent pathologic phenomenon. If this assumption were true, then mechanical extraction of fluid (i.e., ultrafiltration therapy) would be expected to portend positive impact on renal hemodynamics and function through improvement in cardio-circulatory physiology and reduction in neurohormonal activation. However, currently available ultrafiltration trials, whether in acute heart failure (AHF) or in CRS, have so far failed to show any improvement in renal function; they have reported no impact or even observed adverse renal outcomes in this setting. Moreover, the presence or absence of renal dysfunction seems to affect the overall safety and efficacy of ultrafiltration therapy in AHF. This manuscript briefly reviews cardiorenal physiology in AHF and concludes that therapeutic options for CRS should not only target cardio-circulatory status of the patients, but they need to also have the ability of addressing the adverse homeostatic consequences of the associated decline in renal function. Peritoneal dialysis (PD) can be such an option for the chronic cases of CRS as it has been shown to provide efficient intracorporeal ultrafiltration and sodium extraction in volume overloaded patients while concurrently correcting the metabolic consequences of diminished renal function. Currently available trials on PD in heart failure have shown the safety and efficacy of this therapeutic modality for patients with chronic CRS and suggest that it could represent a pathophysiologically and conceptually relevant option in this setting.